Introduction - Gabriel, University of Malaya, Malaysia, Sharmani Patricia (Asiatic: IIUM Journal of English Language and Literature, 2016)
I am honoured to be a part of this issue of Asiatic and writing the Introduction to this section of four essays, which were originally presented as papers at the colloquium on â€œJourneys of/toward Identityâ€ convened on 15 October 2015 by the Department of English, Faculty of Arts and Social Sciences, University of Malaya in Kuala Lumpur. Professor Mohammad A. Quayum delivered Colloquium 2015â€™s opening keynote address. The articles that appear here have been specifically selected and revised for publication in Asiatic. They also help situate and (re)historicise a theoretically abstracted concept like â€œidentity.â€